Microcircuit ladder network with pencil - Dietrich, T. A. (1950)
Resistor ladders are electrical circuits made from repeating units of resistors. This photograph is part of a series of marketing images used to demonstrate the small size of Helipot products.
Keywords: Ladder networks; Pencils; Beckman Instruments, Inc.